ANALISIS TINGKAT RISIKO KELELAHAN OPERATOR DUMP TRUCK DI PT. BP DESA TUMBANG OLONG I KECAMATAN UUT MURUNG KABUPATEN MURUNG RAYA - Gunawan, Lilik; Sukmawatie, Neny; Murati, Ferra; Nuranisa, Arum Chofifah (Jurnal Teknika: Jurnal Teoritis dan Terapan Bidang Keteknikan, 2024)
This study aims to analyze the level of fatigue risk in dump truck (DT) operators at PT. BP located in Tumbang Olong I Village, Uut Murung District, Murung Raya Regency, Central Kalimantan Province. DT operators at PT. BP are involved in hauling work with a distance of approximately 140 km from stockpile to port. The hauling which takes approximately 6 hours is carried out with a certain trip system and speed limit. Using a qualitative approach and descriptive analysis, this study identified fatigue risk factors including work duration, work shift, rest time, workload, work environment, physical condition, sleep time, stress, and food/drink consumption patterns. Primary data (age, length of service, education, and questionnaire) were combined with secondary data (location map and delivery area, regional geological map, local geological map of IUP research area). Fatigue risk was measured through the SNI ISO 31000 standard, with risk mapping using a 5x5 risk matrix. The results of the study showed that fatigue factors consist of work and non-work factors, with four categories of risk levels: low (workload), medium (sleep time, physical condition), high (rest time, work shift, work environment, stress), and very high (work duration, food/drink). Based on these findings, company intervention is needed to control risks that are in the high and very high categories